Ecoprint Ecoprint: Keindahan Batik Alam Berbalut Kreativitas Ibu-Ibu Dusun Sawah Desa Krambilsawit - Salma, Zidni; Mubarokah, Raka; Mursyid, Fadhilah; Mauludin, Iman; Muhyiddin, Muhammad Hakim (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Ecoprint is a natural dyeing technique that uses plant materials like stems, leaves, and flowers to create patterns on fabric. The training activity, conducted on 9 August 2024, aimed to teach participants how to create ecoprint designs using the pounding technique. The training took place in Sawah Hamlet Hall, Krambilsawit Village, Saptosari District, Gunungkidul. It was part of the KKN 127 Batch 144 collaboration between UIN Sunan Kalijaga and UIN Syarif Hidayatullah Jakarta. The program aimed to empower local women by leveraging their natural resources and fostering creativity. The ecoprint training was a success, as evidenced by the enthusiastic participation of the women. They found the program valuable for developing their creativity and skills. The training not only helped them learn a new technique but also encouraged them to appreciate and utilize the natural resources in their community.